Protection of Indigenous Peoples' Rights in Forest Areas: A Normative Legal Analysis of the Seizure of Indigenous Territories - Rima Homesty; Rahadi Wasi Bintoro (LEGAL BRIEF, 2026)
The takeover of indigenous peoples' land rights by the state or corporations remains a legal issue that requires special attention. Indigenous communities, who manage forest areas such as customary land rights for generations, often face challenges from the state, which acts as the primary authority over forest areas. This study aims to analyze the forms of protection for indigenous peoples' rights using a normative approach. The method used in this study is normative juridical, utilizing literature study techniques by examining laws and legal doctrines related to the recognition of indigenous peoples' rights and rights to traditional territories. This study found that the recognition of indigenous peoples' rights has been normatively accommodated in the constitution and related regulations, but its implementation faces challenges in the form of overlapping sectoral policies and low administrative recognition of indigenous community territories. Therefore, reconstructive efforts are needed in the form of regulatory harmonization and legal recognition of indigenous peoples' territories so that the protection of indigenous peoples' rights in forest areas can be implemented effectively and fairly